A Review of Chlamydial Infections in Wild Birds - Helena S. Stokes; Mathew L. Berg; Andrew T. D. Bennett (Pathogens, 2021)
The Chlamydia are a globally distributed genus of bacteria that can infect and cause disease in a range of hosts. Birds are the primary host for multiple chlamydial species. The most well-known of these is Chlamydia psittaci, a zoonotic bacterium that has been identified in a range of wild and domesticated birds. Wild birds are often proposed as a reservoir of Chlamydia psittaci and potentially other chlamydial species. The aim of this review is to present the current knowledge of chlamydial infections in wild avian populations. We focus on C. psittaci but also consider other Chlamydiaceae and Chlamydia-related bacteria that have been identified in wild birds. We summarise the diversity, host range, and clinical signs of infection in wild birds and consider the potential implications of these infections for zoonotic transmission and avian conservation. Chlamydial bacteria have been found in more than 70 species of wild birds, with the greatest chlamydial diversity identified in Europe. The Corvidae and Accipitridae families are emerging as significant chlamydial hosts, in addition to established wild hosts such as the Columbidae. Clarifying the effects of these bacteria on avian host fitness and the zoonotic potential of emerging Chlamydiales will help us to understand the implications of these infections for avian and human health.